Strategi Self-Management dan Coping Religius Dalam mengatasi Stres Akademik Mahasiswa Baru - Muhammad Hafidz Ilmi; Muhammad Fikri Haekal (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2026)
The transition period from secondary education to higher education often triggers academic stress among first-year students due to significant changes in learning paradigms. This study aims to explore in depth the dynamics of academic stress, the implementation of self-management strategies, and the role of religious coping as an adaptive mechanism among first-year students at Universitas Sapta Mandiri. The study employed a descriptive qualitative method, with data collected through open-ended questionnaires administered to first-year students. The data were analyzed using thematic analysis techniques through the stages of data reduction, categorization, data presentation, and conclusion drawing. The study involved six first-year students. The findings reveal that the primary stressors stem from the burden of scientific paper assignments and the demands of self-directed learning. Students mitigated these pressures through self-management strategies in the form of time regulation and behavioral regulation. The main finding of this study is the integration between technical self-management and religious coping (ritual practices and the concept of tawakkal), which together form psychospiritual resilience. This synergy enables students to transform academic burdens into a meaningful and stable process of personal growth.